Gulf of Mexico Seafood Harvesters, Part 2: Occupational Health-Related Risk Factors - Melvin L. Myers; Robert M. Durborow; Andrew S. Kane (Safety, 2018)
The purpose of this literature review, the second in a series following one on traumatic injuries and fatigue, is to identify potential health hazards to inform a study of occupational health and safety among fish harvesters in the Gulf of Mexico (GoM). Fish harvesters are potentially at a high risk of occupational illnesses in GoM fisheries. GoM fishers engage in harvesting shrimp, finfish, oysters, crabs, and clams. Method: The method is a narrative literature review. Search terms that included safety, seafood, occupational, fishing, oyster, clam, shrimp, crab, and GoM were used to identify relevant literature in combination (i.e., a string search). Results: A total of 53 manuscripts were reviewed, of which only two regarded the GoM, but 19 were from the US Atlantic Coast. Musculoskeletal disorders are widespread across the fishing sector. Other hazards include bites and stings from aquatic animals (some of which may be life-threatening), vessel engine noise, dermatoses, and other skin afflictions (including possible strep infection of wounds), solar ray-induced eye diseases, and respiratory exposures (such as to protein aerosols) that can cause asthma. Diving poses multiple breathing and other hazards. Conclusion: While fish harvesters are protected from respiratory problems when working on the well-ventilated deck and dermal hazards by wearing gloves, musculoskeletal, bite and sting, ocular, engine-related hearing loss, and skin, lip, and eye cancer hazards are potentially serious risks among GoM fish harvesters.